Rad girls can : stories of bold, brave, and brilliant young women - Schatz, Kate (Ten Speed Press, 2018)
Highlights a selection of young women who have used their boldness and bravery to overcome obstacles and accomplish great things. Subjects range from Misty Copeland and Yusra Mardini to Helen Keller and Joan of Arc.